Early Modern Consumption History: Current Challenges and Future Perspectives - Ryckbosch, Wouter (BMGN - Low Countries Historical Review, 2015)
Stimulated by wide-ranging theories on its cultural and economic significance, the history of early modern consumption in the Low Countries has received a remarkable amount of attention in historiography during the last three decades. During this period the growing body of empirical evidence, as well as shifting theoretical frameworks, have gradually altered our understanding of early modern patterns of consumption, their causes and consequences. The current article presents a review of the main tendencies in the field of early modern consumption history, and the challenges to this historiographical field these have presented. Based on these challenges, the article suggests new avenues for future research. Vroegmoderne consumptiegeschiedenis. Hedendaagse uitdagingen en toekomstperspectieven Gestimuleerd door verstrekkende nieuwe theorieën over haar culturele en economische betekenis, heeft de historiografie met betrekking tot vroegmoderne consumptie in de Nederlanden op opmerkelijk veel aandacht mogen rekenen tijdens de voorbije drie decennia. Daarbij hebben zowel een groeiende beschikbaarheid van empirisch bronnenmateriaal, als verschuivende theoretische perspectieven, geleidelijk aan ons begrip van vroegmoderne consumptiepatronen, en hun oorzaken en gevolgen grondig veranderd. Het huidige artikel biedt een overzicht van de belangrijkste tendensen in het domein van de vroegmoderne consumptiegeschiedenis, gevolgd door nieuwe uitdagingen en toekomstperspectieven.